2019
DOI: 10.1101/679241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstructing neural representations of tactile space

Abstract: Psychophysical experiments have demonstrated large and highly systematic perceptual distortions of tactile space. We investigated the neural basis of tactile space by analyzing activity patterns induced by tactile stimulation of nine points on a 3 x 3 square grid on the hand dorsum using functional magnetic resonance (fMRI). We used a searchlight approach within pre-defined regions of interests (ROIs) to compute the pairwise Euclidean distances between the activity patterns elicited by tactile stimulation. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…We explored tactile space organization across IFD patients using a novel behavioral paradigm, which allowes quantification of distortions in tactile spatial perception and matches cortical tactile space organization in the primary somatosensory cortex. 7,12 Clearly, stimulus size judgments differed across orientations in controls and in groups of patients with CD, BSP/Meige syndrome, and FHD, replicating distortions of tactile space previously shown for healthy individuals. 7 However, contrary to our hypothesis, we found that there was neither change in the magnitude of anisotropy nor in the axis at which tactile distances were perceived as largest or in the global stimulus size estimation between groups.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We explored tactile space organization across IFD patients using a novel behavioral paradigm, which allowes quantification of distortions in tactile spatial perception and matches cortical tactile space organization in the primary somatosensory cortex. 7,12 Clearly, stimulus size judgments differed across orientations in controls and in groups of patients with CD, BSP/Meige syndrome, and FHD, replicating distortions of tactile space previously shown for healthy individuals. 7 However, contrary to our hypothesis, we found that there was neither change in the magnitude of anisotropy nor in the axis at which tactile distances were perceived as largest or in the global stimulus size estimation between groups.…”
Section: Discussionsupporting
confidence: 74%
“…7 Indeed, perceptual distortions of tactile space match cortical tactile space organization in the primary somatosensory cortex. 12 Previous literature shows impaired tactile spatial acuity in different forms of IFD [13][14][15][16][17] that is suggested to reflect a - --------------------------------------------------------degradation of somatotopic organization in the somatosensory cortex. [18][19][20][21][22] We therefore employed a novel behavioral paradigm to examine the perceptual organization of tactile space in IFD.…”
mentioning
confidence: 97%
“…The motivation for developing such technologies is predicated on the assumption that humans can perceive the spatial and temporal features of whole hand tactile stimuli in the same way we would perceive equivalent visual stimuli with our eyes. Although the spatial and temporal features of such whole hand tactile stimuli prompt obvious parallels with visual stimuli (shapes, lines, motion), touch is a distinct sensory domain, processed in distinct cortical regions ( Gardner, 1988 ; Pei et al., 2010 , 2011 ; Tamè et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing anisotropy, therefore, provides a unique opportunity to capture spatial processing of tactile input in the context of a specific body part. Tactile distance judgements are particularly relevant to evaluate given recent work showing that distortions in tactile distance perception at the hand are mirrored in the neural representation in S1 ( Tamè et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%